On the divergence of triangular and eccentric spherical sums of double Fourier series. (11th March 2016) - Karagulyan, G A
Abstract: We construct a continuous function on the torus with almost everywhere divergent triangular sums of double Fourier series. We also prove an analogous theorem for eccentric spherical sums. Bibliography: 14 titles.